2016
DOI: 10.1088/0031-9155/61/22/7919
|View full text |Cite
|
Sign up to set email alerts
|

Track-average LET of secondary electrons generated in LiF:Mg,Ti and liquid water by 20–300 kV x-ray,137Cs and60Co beams

Abstract: Electrons generated in matter by photons could be a fundamental basis for an adequate analysis of radiation effects and damage. We have studied separately the 'primary electrons' generated directly by photons from the 'secondary electrons' (SE) produced by electron-electron interactions. In this work, track-average linear energy transfer, [Formula: see text], of SE in LiF:Mg,Ti and liquid water produced by twelve photon energy beams from 20 kV x-ray to Co gamma rays have been investigated using the EGSnrc Mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 27 publications
(40 reference statements)
3
24
0
Order By: Relevance
“…In the EGSnrc code, it is possible to score the "total electron fluence" (TEF) where all electrons generated by photons and by electron-electron interactions are counted; the "primary electrons" (PE) that compute all electrons generated by photons during the interaction and "secondary electrons" (SE) which include all electrons produced due to electron-electron interactions. We are particularly interested on the SEs since our previous work for LiF suggested that the LET of SEs better describes the experimental observation of the dosimeter response than the LET of TEF 8 . This is explained by the fact that SEs have very short range (order of nanometers) and cannot move far away from their origin, so consequently deposit their energy locally and activate more colour centers within the film sensitive volume.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the EGSnrc code, it is possible to score the "total electron fluence" (TEF) where all electrons generated by photons and by electron-electron interactions are counted; the "primary electrons" (PE) that compute all electrons generated by photons during the interaction and "secondary electrons" (SE) which include all electrons produced due to electron-electron interactions. We are particularly interested on the SEs since our previous work for LiF suggested that the LET of SEs better describes the experimental observation of the dosimeter response than the LET of TEF 8 . This is explained by the fact that SEs have very short range (order of nanometers) and cannot move far away from their origin, so consequently deposit their energy locally and activate more colour centers within the film sensitive volume.…”
Section: Methodsmentioning
confidence: 99%
“…This is explained by the fact that SEs have very short range (order of nanometers) and cannot move far away from their origin, so consequently deposit their energy locally and activate more colour centers within the film sensitive volume. The simulation was performed considering the same parameters selected in our previous work 8 , i.e. 512 keV and 1 keV electron transport cut-off (ECUT) and photon transport cut-off (PCUT), respectively with Bound Compton, spin effects and Rayleigh scattering turned on.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the use of small radiation fields (60 mm down to 5 or 4 mm diameter) should impart dose to the target volume in a sure manner. The physical concept of small radiation fields in radiotherapy is strongly correlated to the high-ionization density problem caused by the variation of the electron fluence spectra in the lateral direction and the small range of the electrons generated in the field [1]. Consequently, the determination of the absorbed dose in these fields remains a challenging task compared to the fields used in conventional radiotherapy (square fields from 4 cm to 40 cm).…”
Section: Introductionmentioning
confidence: 99%